Production and Immunogenicity of Soluble Plant-Produced HIV-1 Subtype C Envelope gp140 Immunogens - Margolin, Emmanuel; Chapman, Rosamund; Meyers, Ann E.; van Diepen, Michiel T.; Ximba, Phindile; Hermanus, Tandile; Crowther, Carol; Weber, Brandon; Morris, Lynn; Williamson, Anna-Lise; Rybicki, Edward P. (Frontiers in Plant Science, 2019)
The development of effective vaccines is urgently needed to curb the spread of human immunodeficiency virus type 1 (HIV-1). A major focal point of current HIV vaccine research is the production of soluble envelope (Env) glycoproteins which reproduce the structure of the native gp160 trimer. These antigens are produced in mammalian cells, which requires a sophisticated infrastructure for manufacture that is mostly absent in developing countries. The production of recombinant proteins in plants is an attractive alternative for the potentially cheap and scalable production of vaccine antigens, especially for developing countries. In this study, we developed a transient expression system in Nicotiana benthamiana for the production of soluble HIV Env gp140 antigens based on two rationally selected virus isolates (CAP256 SU and Du151). The scalability of the platform was demonstrated and both affinity and size exclusion chromatography (SEC) were explored for recovery of the recombinant antigens. Rabbits immunized with lectin affinity-purified antigens developed high titres of binding antibodies, including against the V1V2 loop region, and neutralizing antibodies against Tier 1 viruses. The removal of aggregated Env species by gel filtration resulted in the elicitation of superior binding and neutralizing antibodies. Furthermore, a heterologous prime-boost regimen employing a recombinant modified vaccinia Ankara (rMVA) vaccine, followed by boosts with the SEC-purified protein, significantly improved the immunogenicity. To our knowledge, this is the first study to assess the immunogenicity of a near-full length plant-derived Env vaccine immunogen.